ASEAN COMMUNITY SEMINAR HELPS TO INCREASE PUBLIC AWARENESS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 15 April 2015 The ASEAN Community Seminar is deemed as the best platform to raise public awareness regarding the implementation of the ASEAN Community and the role of Malaysia as the ASEAN Chair in 2015. The DirectorGeneral of ASEANMalaysia National Secretariat, Dato’ Muhammad Shahrul Ikram Yaakob, representing the Deputy Foreign Minister of Malaysia said, the level of public awareness among Malaysians on the ASEAN community is still low.